PENGARUH SISTEM ADMINISTRASI PERPAJAKAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Supriatiningsih Supriatiningsih Supriatiningsih (JURNAL AKUNTANSI, 2023)
The purpose of this study is to identify and analyze the impact of tax administration systems and taxpayer attitudes on tax compliance. This study is quantitative and uses primary data from the distribution of questionnaires. Sampling used targeted sampling and the number of respondents for this study was 90 respondents at Pt. Perfect Health Indonesia. Data processing using SPSS version 22. The results of the surveys conducted show that tax administration systems and taxpayer perceptions have a significant impact on tax compliance. At the same time, administrative and compliance systems influence taxpayer compliance. The activities and programs of the tax administration system influence taxpayer perceptions and thereby improve taxpayer compliance. Improved taxpayer compliance increases government revenue in the tax area